Uso de la historieta para mejorar el hábito de la lectura en el área de comunicación de los alumnos de sexto año de educación básica de la Escuela 24 de Mayo de la Parroquia San Juan - Garcia Villamar, Mariana del Carmen (2020)
The research entitled "USE OF THE HISTORY TO IMPROVE THE READING HABIT IN THE AREA OF COMMUNICATION OF THE SIXTH YEARS OF BASIC EDUCATION OF THE SCHOOL MAY 24 OF THE SAN JUAN PARISH", resulted in the extent to which Story reading can motivate and develop a taste for reading in students; Essential resource to improve learning. For this reason, 18 students from a population of 50 in total will be taken as an intentional sample, to which a previous test (survey) will be applied, after which sessions with reading stories will be developed; then apply a post test (survey); The research was quantitative, with an experimental design. According to Spearman's Rho correlation analysis, the hypothesis is positive, since there is a significant correlation between the independent and the dependent variable, which is equal to 72.8%. According to the results, the Bilateral Sig value 0.001 is less than 0.05; therefore the null hypothesis is rejected.